Improving Experimentation Skills through the Implementation of Project Based Learning: Analysis of Creative Thinking Skills - Puspitasari, Septa Dwi; Atmojo, Idam Ragil Widianto; Daryanto, Joko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research aims to: (1) determine the effect of Project Based Learning (PjBL) on students' experimentation skills; (2) determine the influence of creative thinking skills on students' experimentation skills; (3) knowing the interaction between Project Based Learning (PjBL) and creative thinking skills on students' experimentation skills. The subjects of this research were all fourth grade elementary school students. This research uses a quantitative type of research with a quasi-experimental research design that provides pretests and posttests to the control class and experimental class groups. The research instruments used were performance to measure students' experimentation skills and written tests to measure students' creative thinking skills. Data analysis prerequisite tests include normality tests, homogeneity tests, and balance. Hypothesis testing uses a two-way ANOVA test with different cells. The results of this research show that (1) Project Based Learning (PjBL) influences students' experimentation skills; (2) Creative thinking skills influence students' experimentation skills; (3) The application of Project Based Learning (PjBL) has an effect on students who have high creative thinking skills. The conclusion of this research is that there is an influence of Project Based Learning on experimentation skills in science learning in terms of creative thinking skills